Endoscopic Adipofascial Radial Forearm Free Flap Reconstruction of the Skull Base: A Technical Update - Pipkorn, Patrik; Lee, Jake J.; Zenga, Joseph; Chicoine, Michael R. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective While most defects after endoscopic endonasal resections can be closed with local or locoregional options, rare cases require free tissue transfer. In this setting, while minimally invasive techniques have been described, the essential procedural details are lacking. The objective of this report is to describe several key technical modifications to free flap harvest and endoscopic-assisted inset which decrease morbidity and improve reliability and efficiency.Methods A retrospective chart review was performed of consecutive patients treated at Washington University in St. Louis with endoscopic free flap reconstruction through a Caldwell–Luc/transbuccal approach between January 2016 and September 2019.Results A total of six patients underwent adipofascial radial forearm free flap with this technique, five for recalcitrant cerebrospinal fluid leak or pneumocephalus and one for osteoradionecrosis. All flaps survived and there were no flap-related complications. Five patients (83%) achieved successful healing and separation of the sinonasal cavity and intracranial space. One patient developed recurrent pneumocephalus. Three key technical modifications were identified that improve efficiency and reliability of flap delivery and inset: (1) use of an adipofascial radial forearm flap, without skin paddle; (2) wide resection of the anterior and lateral maxillary face to facilitate flap delivery; and (3) precise defect measurement and flap contouring prior to inset to prevent any need to debulk the flap in situ.Conclusion Endoscopic adipofascial radial forearm free flap delivered to the skull base through a Caldwell–Luc/transbuccal corridor is a feasible option with a high success rate and low morbidity when other reconstructive attempts have failed.
Keywords: endoscopic; endonasal; skull base; free flap; reconstruction